Treatment of femoral shaft fractures in young children by Ender’s nail: indications & complications - Nikose, Sunil; Arora, Mridul; Singh, Pradeep K; Shrivastava, Sandeep; Taywade, Shounak (International Journal of Research in Medical Sciences, 2017)
Background: Treatment of femoral fractures in age group of 6 – 12 years is controversial. Operative treatment is becoming better accepted. Various modalities of fixation include plate osteosynthesis, External fixation; Antegrade locked nailing, and flexible intramedullary nailing. Methods: 60 children aged 6-12 years (Average age – 8.2 years) with 66 femoral diaphyseal fractures (61 closed and 05 open) in 60 patients were managed with closed Ender’s nailing. Pathological fractures due to unicameral bone cyst were evident in 5 patients. Femoral shaft fractures at the level proximal to distal three fifth with canal diameter of ≥ 6mm were included in the study. Out of 66 traumatic fractures 42 fractures had stable pattern and 19 had unstable fracture pattern. The results were evaluated clinically and radiologically. Results: All the 42 stable femoral fractures showed bridging callus in a mean time of 3.83 weeks (2.5 to 6.5 weeks). Full weight bearing was possible in a mean time of 4.19 weeks. Radiological union was seen in a mean time of 9.4 weeks. 34 fractures were evaluated by scanogram one year after injury and they revealed lengthening of 0.3cms. All the children returned to their previous level of activities. All the 19 unstable femoral fractures showed bridging callus in a mean time of 5.53 weeks (4 – 8 weeks). Full weight bearing was possible in a mean time of 6.21weeks. Radiological union was seen in a mean time of 12 weeks. 8 patients were readmitted for adjunctive procedures like nail impaction, traction and cast immobilization. 20% patients with unstable group had shortening of 1.3cms and 20% had external rotation of lower limb. Conclusions: Ender’s nailing is simple, cost-effective and minimally invasive procedure in 6-12 years of age. It offers stable fixation with rapid healing. There is prompt return of child to normal activity.